How does the scaling for the polymer chain in the dissipative particle dynamics hold? - Ilnytskyi, J.M.; Holovatch, Yu. (Condensed Matter Physics, 2007)
We performed a series of simulations for a linear polymer chain in a solvent using dissipative particle dynamics to check the scaling relations for the end-to-end distance, radius of gyration and hydrodynamic radius in three dimensions. The polymer chains of up to 80 beads in explicit solvent of various quality are studied. To extract the scaling exponent , the data are analyzed using linear fits, correction-to-scaling forms and analytical fits to the histograms of radius of gyration distribution. For certain combinations of the polymer characteristics and solvent quality, the correction-to-scaling terms are found to be essential while for the others these are negligibly small. In each particular case the final value for the exponent ν was chosen according to the best least-squares fit. The values of ν obtained in this way are found within the interval ν = 0.55 ÷ 0.61 but are concentrated mostly around 0.59, which is very close to the best known theoretical result ν = 0.588. The existence of this interval is attributed both to the peculiarities of the method and to the moderate chain lengths being simulated. Within this shortcoming, the polymer chain in this kind of modeling is found to satisfy the scaling relations for all three radii being considered.